From Good Deeds to Tax Strategies: The Interplay of CSR, Profitability, and Leverage on Tax Avoidance in Indonesia - Raden Roro Diana Atika Ghozali; Rissa Anandita; Naila Hanum; apip (Indonesian Journal of Auditing and Accounting, 2026)
This research investigates the influence of Corporate Social Responsibility, profitability, and leverage on tax avoidance strategies within Indonesian companies listed in the Bloomberg FEB Undip database between 2016 and 2023. Tax avoidance is quantified using the Cash Effective Tax Rate. The study employed purposive sampling to select its sample. Findings indicate that CSR, profitability, and leverage have not been the primary determinants of tax avoidance behavior among Indonesian companies. Furthermore, the study observed considerable variability in CSR and leverage disclosures, alongside a tendency towards significant tax avoidance in certain firms.